Circumcision versus preputioplasty for balanitis xerotica obliterans: a randomised controlled feasibility trial. (11th July 2021) - Lansdale, Nick; Arthur, Felicity; Corbett, Harriet J.
Abstract : Objectives: To determine: (i) feasibility for a randomised controlled trial (RCT) comparing circumcision to preputioplasty and intralesional triamcinolone (PIT) to treat balanitis xerotica obliterans (BXO) and (ii) patient outcomes to inform future study design. Patients and Methods: Approval was obtained from the UK Health Research Authority and local Research Ethics Committee (Reference 16/NW/0364) and the trial protocol registered with ClinicalTrials.gov (NCT02854995). A total of 20 boys (aged 2–16 years) with BXO were randomised to either circumcision or PIT (online parallel group 1:1 allocation, non‐blinded). Exclusion criteria were: (i) previous penile surgery and (ii) contraindication for either treatment. Follow‐up (including satisfaction questionnaire) was at 6 weeks, 3 and 12 months. Data are presented as median (interquartile range [IQR]), continuous variables were compared by t ‐test. Results: A total of 54 boys were approached over 18 months: 23 (45%) were recruited and randomised. The commonest reason for non‐entry was treatment preference: 12 preferred circumcision, 18 preferred PIT. Four patients withdrew after randomisation, three did not want circumcision and one did not want PIT. The groups were similar in terms of age (median [IQR] 11 [6–12] vs 8 [7–10] years, P = 0.53) and duration of symptoms (median [IQR] 6 [6–15] vs 6 [2–24] months, P = 0.77). There were no protocol breaches, serious adverse events or postoperative meatal stenosis. There was one self‐resolving haematoma after PIT and one suture granuloma after circumcision. Two boys went on to have a circumcision after PIT. Overall, satisfaction levels were high for both groups. Conclusion: A definitive RCT of circumcision vs PIT for BXO appears feasible, with 39% of those approached completing the trial. More families preferred PIT. A robust comparison in the form of a multicentred RCT is required.